1992
DOI: 10.3109/03008209209016818
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bovine synovial fluid lubricating factor III. The interaction with hyaluronic acid

Abstract: Although hyaluronate is not a boundary lubricant in cartilaginous and latex:glass bearings, a distinct interaction with purified synovial lubricating factor (PSLF) was demonstrated by three means: 1) enhancement of lubricating ability in an artificial test system; 2) viscometry; 3) electron microscopy. The interaction was of a physical rather than a specific chemical type; it varied with the degree of purification of PSLF and of hyaluronate. The interaction accounts for retention of the relatively small PSLF m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 14 publications
6
71
0
2
Order By: Relevance
“…Similar SF constituents have been used in several previous studies examining their lubricating function (12,18,21,(23)(24)(25)(26), and future studies may examine the friction-lowering effects of other specific forms of SF constituents. Additional studies examining the structure-function relationship of SF constituents contributing to boundary lubrication, both alone and in combination, may provide the framework for the potential complete recapitulation of the boundary-lubricating ability of whole SF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar SF constituents have been used in several previous studies examining their lubricating function (12,18,21,(23)(24)(25)(26), and future studies may examine the friction-lowering effects of other specific forms of SF constituents. Additional studies examining the structure-function relationship of SF constituents contributing to boundary lubrication, both alone and in combination, may provide the framework for the potential complete recapitulation of the boundary-lubricating ability of whole SF.…”
Section: Discussionmentioning
confidence: 99%
“…Jay et al (21) previously reported that HA and PRG4 acted synergistically, with HA enabling PRG4 to lubricate under higher contact pressures at a latex-glass interface under boundary-lubricating conditions. In that study, hydrophobic attraction of PRG4 molecules along the length of HA was suggested as a possible mechanism for this interaction, although PRG4 does contain other putative binding domains as well (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations